DIGITAL LITERACY AND ITS IMPACT ON LANGUAGE LEARNING IN PRIMARY SCHOOLS - Andriyani, Dini; Nazwa, Farah; Maharani, Nur Indah; Aminarti, Ria; Purba, Susilawati; Juliati, Juliati (Universitas Negeri Medan, 2025)
The rapid advancement of information and communication technology has made digital literacy an essential competence in contemporary education. The ability to access, evaluate, and utilize credible information sources has become increasingly critical in response to the accelerated growth of digital technologies. In the context of education, digital literacy encompasses the capacity to access, analyze, create, reflect on, and act upon information using digital devices, multiple modes of expression, and diverse communication strategies. This article presents a conceptual and literature-based analysis of the impact of digital literacy on language learning in primary schools, as well as the challenges associated with its implementation. The findings indicate that digital literacy contributes positively to language learning by supporting instructional processes, enabling learners to distinguish valid and relevant learning resources, and encouraging teachers to develop more innovative and productive digital learning media. However, the effective integration of digital literacy in language instruction requires teachers not only to master digital tools and software but also to develop advanced competencies, including content production skills, visual literacy, hypertextual navigation, information evaluation, and socio-emotional skills.Overall, digital literacy plays a crucial role in enhancing language learning and fostering essential twenty-first-century skills among primary school students.